2012
DOI: 10.1111/j.1524-475x.2012.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the host inflammatory response to wound infection: An in vivo study of Klebsiella pneumoniae in a rabbit ear wound model

Abstract: Wound infection development is critically dependent on the complex interactions between bacteria and host. Klebsiella pneumoniae has become an increasingly common wound pathogen, but its natural history within wounds has never been studied. Using a validated, in vivo rabbit ear model, wounds were inoculated with K. pneumoniae at different concentrations (10²-10⁷ colony-forming units) with measurement of viable and nonviable bacterial counts, histological wound-healing parameters, and host inflammatory gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
1
35
0
1
Order By: Relevance
“…The uninfected controls healed quicker than the P. aeruginosa infected wounds, which were confirmed to be in a biofilm by the presence of microcolonies or aggregates of cells, as shown with SEM. Seth et al 25 also used a rabbit ear model to study the effect of Klebsiella pneumoniae on wound healing, confirming biofilm as cellular aggregates by SEM. Later, Seth et al 26 developed dermal punch wounds in white rabbit ears and inoculated them with K. pneumoniae, S. aureus, or P. aeruginosa.…”
mentioning
confidence: 94%
“…The uninfected controls healed quicker than the P. aeruginosa infected wounds, which were confirmed to be in a biofilm by the presence of microcolonies or aggregates of cells, as shown with SEM. Seth et al 25 also used a rabbit ear model to study the effect of Klebsiella pneumoniae on wound healing, confirming biofilm as cellular aggregates by SEM. Later, Seth et al 26 developed dermal punch wounds in white rabbit ears and inoculated them with K. pneumoniae, S. aureus, or P. aeruginosa.…”
mentioning
confidence: 94%
“…Outcomes such as impairment of epithelialization, overabundance of granulation tissue, and a hyperinflammatory state are interesting. 8,26,[40][41][42][43] However, reported studies involve short-term infection disallowing prolonged interaction between polymicrobial pathogens and the host. In that respect, the rabbit ear model suffers from limitations comparable to those discussed for the rodent models.…”
Section: In Vivo Biofilm Modelsmentioning
confidence: 99%
“…2 Persistent infection may not only arrest growth of the repairing tissue but it is also known to substantially modify the inflammatory response compromising timely resolution. [3][4][5] The influence of wound infection on the healing process may depend on the following factors: (1) wound etiology, dimension, tissues involved, and anatomical location, 6,7 (2) host factors and response, 8,9 (3) composition of polymicrobial species, 10,11 and (4) state of infection, that is, planktonic and/or biofilm. Biofilm-infected wounds suffer from compromised closure.…”
Section: Introductionmentioning
confidence: 99%
“…8) Seth et al also demonstrated that impaired host immunity allows bacteria to establish wound infection. 32) In contrast, Kanno et al reported accelerated wound healing following PAO-1 inoculation 33) or 3OC12-HSL administration, 34) thus supporting the latter situation. Future studies are needed to explore this hypothesis.…”
Section: Discussionmentioning
confidence: 90%